An analysis of available biomarker data for targeting cyclin-dependent kinases 4 and 6 (CDK4/6) in breast cancer. Issue 3 (4th May 2019) - Duso, Bruno Achutti; Ferraro, Emanuela; Mazzarella, Luca; Dagostim Jeremias, Camila; Curigliano, Giuseppe
ABSTRACT: Introduction : Inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6i) are a standard of care for advanced estrogen receptor (ER)–positive breast cancer in combination with hormonal therapy. Recent data from large trials comprising these agents in different settings show that a proportion of patients do not actually achieve a clinical benefit from this class, without a clear-cut panorama of predictive biomarkers. Here, clinical and preclinical evidence regarding plausible alterations that have been studied as possible candidates for better steering the indications of CDK4/6i in clinical practice are reviewed and analyzed. Areas covered : We explored cyclin D-related aberrations, ESR1 mutational profile, pRb levels/loss of RB1 function, cyclin E1-E2 overexpression, CDK6 amplification, PIK3CA/AKT/mTOR pathway interactions, and CDKN2A loss/CDK2 activity. Expert opinion : The complex molecular pathway involving cell cycle regulation still hampers the validation of a single marker to rationally select patients who would benefit the most from CDK4/6i and avoid futile toxicity. We perceive that, through a combination of assembled molecular alterations, both patient and resource allocation can be optimized. In the meanwhile, paired and reproducible tumor analyses, as well as early ctDNA dynamics, are strongly supported through clinical trials.